Exploring the profiles of pre-service teachers technological pedagogical content knowledge (TPACK) on earth and space science offline and online course - Diki Rukmana; Sri Lestari Handayani (Universitas PGRI Madiun, 2021)
This study reveals the comparison of the TPACK profiles of pre-service elementary school teachers in the Earth and Space Science (ESS) offline and online lectures. The sample consisted of 97 students who took offline lectures in the 2018/2019 academic year and 85 students who took online lectures in the 2019/2020 academic year. The research instrument consisted of 38 questionnaire items that assessed the self-efficacy of the TPACK-21 components. The correlation analysis results show that in all aspects of basic knowledge and secondary knowledge, ESS online courses provide better results in developing TPACK abilities than offline courses. However, the SEM analysis results show that the structure of the TPACK ability development model in the offline class appears to be more stable than the online class. This indicates a need for further development in online learning strategies and approaches to lead to a more significant contribution to the development of TPACK.